PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PANTUN PADA SISWA KELAS XI JB1 SMK PGRI 4 DENPASAR TAHUN PELAJARAN 2015/2016 - Putu Dessy Fridayanthi; Ni Wayan Rosmita Kumala Dewi (Widyadari : Jurnal Pendidikan, 2019)
This study aims to determine the effectiveness of pantun writing skills in class XI students by applying the Numbered Heads Together (NHT) type of cooperative learning model, and to determine the responses of class XI students in pantun writing learning by applying the Numbered Heads Together (NHT) type of cooperative learning model. The subjects of this class action research were students of class XI JB1 SMK PGRI 4 Denpasar in the 2015/2016 academic year which amounted to 43 students, consisting of 19 female students and 24 male students, the object of the research was the application of the Numbered Heads Together type cooperative learning model (NHT). The research method used is in accordance with the objectives to be achieved, namely 1) research design, 2) research settings, 3) subject and object of research, 4) research procedures, 5) data collection methods, 6) data processing methods, and 7) interesting conclusion. It can be concluded that (1) There is an increase in rhyme writing skills in class XI students. The implementation of the Numbered Heads Together (NHT) type of cooperative learning model increased by 27.91% from 58.14% in the first cycle to 86.05% in the second cycle. (2) There is an increase in the response of students of class XI JB1 SMK PGRI 4 Denpasar in the 2015/2016 academic year on the application of the Numbered Heads Together (NHT) type of cooperative learning model in participating in pantun writing learning.